2021
DOI: 10.1016/j.molcel.2021.09.010
|View full text |Cite
|
Sign up to set email alerts
|

Liquid-liquid phase separation: Orchestrating cell signaling through time and space

Abstract: Cell signaling is a complex process. The faithful transduction of information into specific cellular actions depends on the synergistic effects of many regulatory molecules, nurtured by their strict spatiotemporal regulation. Over the years, we have gained copious insights into the subcellular architecture supporting this spatiotemporal control, including the roles of membrane-bound organelles and various signaling nanodomains. Recently, liquid-liquid phase separation (LLPS) has been recognized as another pote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
85
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(85 citation statements)
references
References 92 publications
0
85
0
Order By: Relevance
“…IDRs often provide a platform for multiple weak interactions in signaling complexes and are more likely to phase separate. An example is the membrane associated pLAT-Grb2-Sos1 condensate in T-cell receptor activation 61 . A fraction of CARP3 at the flagellar tip does not localize at the membrane but colocalizes with the cytoskeletal scaffold protein FLAM8, previously positioned at the plus end of the axonemal microtubules in PCF 15 and also distributed along the flagellum in BSF 62 .…”
Section: Discussionmentioning
confidence: 99%
“…IDRs often provide a platform for multiple weak interactions in signaling complexes and are more likely to phase separate. An example is the membrane associated pLAT-Grb2-Sos1 condensate in T-cell receptor activation 61 . A fraction of CARP3 at the flagellar tip does not localize at the membrane but colocalizes with the cytoskeletal scaffold protein FLAM8, previously positioned at the plus end of the axonemal microtubules in PCF 15 and also distributed along the flagellum in BSF 62 .…”
Section: Discussionmentioning
confidence: 99%
“…For the cGAS-STING signaling, the recent finding that deactylation of cGAS controls full activation of the signaling network is an example of the former [ 219 ]. An example of the latter is the discovery that dsDNA and cGAS interaction may take place in liquid-like droplets [ 220 ]. Interestingly, this phase separation presents a barrier to the negative regulation of the cGAS-STING signaling by removal of the dsDNA by endonucleases such as TREX1 [ 221 ].…”
Section: Dynamic Modeling Of Modulators Of the Cgas-sting Pathwaymentioning
confidence: 99%
“…A large number of studies have shown that LLPS are formed in membraneless aggregates including nuclear spots and stress particles to maintain genome stability, transcriptional regulation, immune-related signal pathways, cellular stress response, cell proliferation, autophagy-related signal pathways, etc. ( Abbas et al, 2021 ; Guo et al, 2021 ; Peng et al, 2021 ; Su et al, 2021 ). Early research shows that abnormal LLPS plays a crucial role in the progression of neurodegenerative diseases ( Zbinden et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%